Zambian indigenous chicken genetic resources: phenotypic characteristics and their production systems among small-scale farmers - Liswaniso, Simushi; Mwambilwa, Kabemba; Odubote, Kolawole; Tyasi, Thobela Louis; Mweni, Mwape; Sun, Xue; Xu, Rifu; Qin, Ning (Frontiers in Veterinary Science, 2024)
This study sought to characterize the Zambian indigenous chickens and profile their production systems to provide a base for a successful improvement breeding program. A structured questionnaire was administered to 177 small-scale farmers. A total of 538 chickens whose mean weight was 1.66 kg were individually phenotyped in Luapula, Muchinga, and Northern provinces of Zambia.Ownership of the indigenous chickens was dominated by females (65.37%), with most (64.31%) having attained primary education. Most housed their chickens in family houses (42.03%). All the farmers let their chickens scavenge for their feed, with 45.58% of them providing basic supplementation. Most (84.10%) farmers bought their breed stock from within their community and had a mean flock size of 12.5 chickens/household, which they mostly (78.09%) kept as free-range. The majority (77.39%) practiced culling, with low productivity being the most common reason for culling (84.45%). Only 59.01% of farmers practiced selective breeding, while 86.22% practiced uncontrolled mating. The age at first mating for cocks and hens was 6.8 months and 6.34 months, respectively, with 6.73 months being the age at first egg. It takes 15.43 days to reach a mean clutch size of 13 eggs. The hatchability and mortality at 8 weeks were 83.44% and 67.57%, respectively. All chickens were sold as live chickens, and the majority (51.59%) of the farmers sold their chickens within the community at 7.23 months. Diseases and predators were the most common challenges affecting farmers in the study area. Consultations with veterinarians, vaccinations, and deworming were uncommon while treating sick chickens mostly using ethnoveterinary medicines was common. The most common qualitative traits were brown (27.88%) and mixed (26.77%) plumage color, white skins (91.45%) and shanks (48.70%), single comb type (91.08%), red earlobe (55.76%), and orange eyes (78.07%). All linear body measurements positively and significantly correlated with the body weight averaging 1.66kgs, an indicator that selection for any of them would result in a corresponding increase in body weight.Principal Component Analysis extracted two components with 69.38% of the total variation. The diversity in phenotypes of these chickens and their production systems indicate huge potential for improvement by implementing breeding programs.